Peran Kepala Sekolah dalam Membentuk Kedisiplinan Siswa SDI Nurul Bayan Kebunagung Sumenep - Nabilah, Fashilatun; El-Faradis, Fayruzah (Faidatuna, 2023)
Role is an action taken by someone in an event or event, in this case, the action taken by the principal in disciplining students at SDI Nurul Bayan Kebunagung Sumenep. Discipline is defined as one's awareness and willingness to comply with all applicable rules and norms. The formulation of the problem in this study is what is the role of the school principal and the supporting and inhibiting factors of the principal's role in disciplining students of SDI Nurul Bayan Kebunagung Sumenep. This study aims to find out how the roles and supporting and inhibiting factors play the role of school principals in disciplining students at SDI Nurul Bayan Kebunagung Sumenep. To better understand the role of the school principal in shaping the discipline of SDI Nurul Bayan students, the researchers used a descriptive qualitative research approach. The method used is the method of interviews, observation, and documentation. From this method, then manage and analyze to obtain data or information. The subjects of this study were taken from school principals, teachers, and students of SDI Nurul Bayan. The results of the research in this thesis are that (1) the principal at SDI Nurul Bayan Kebunagung Sumenep has become a headmaster who has set a good example for his school staff, ( 2) The role of the school principal at SDI Nurul Bayan Kebunagung Sumenep in forming student discipline is quite good, namely by disciplining himself, namely by setting an example, directing and coaching carried out on teachers/staff and students, (3) Factors supporting the role of the principal in SDI Nurul Bayan Kebunagung Sumenep is the existence of support from teachers/staff, support from parents, the existence of rules written in each class, and awareness of the students themselves, while the inhibiting factor for the role of the principal is the delay of students coming to school.